Pengaruh Managerial Ownership, Political Connection, Dan Leverage Terhadap Tax Aggressiveness - Muhammad Nur Fajar; Irwan Setiawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to reveal the effect of managerial ownership, political connection, and leverage on tax aggressiveness. This type of research uses an associative quantitative research method. The population in this study are companies in the Energy sector listed on the Indonesia Stock Exchange in 2021–2024. This study employs a purposive sampling technique. The research population consists of 90 energy sector companies listed on the Indonesia Stock Exchange. After applying the sampling criteria and excluding outliers, 9 companies were selected, yielding a total of 36 observations. Panel data regression analysis was conducted using EViews version 12. The findings reveal that political connection has a positive and significant effect on tax aggressiveness, while managerial ownership and leverage have no significant effect. Simultaneously, managerial ownership, political connection, and leverage significantly influence tax aggressiveness.